VIPP1 Involved in Chloroplast Membrane Integrity Has GTPase Activity in Vitro. Issue 1 (5th April 2018) - Ohnishi, Norikazu; Zhang, Lingang; Sakamoto, Wataru
Abstract : A chloroplast protein known to be involved in membrane biogenesis and maintenance displays a novel type of GTPase activity requiring oligomerization through its N-terminus. Abstract: VESICLE-INDUCING PROTEIN IN PLASTID1 (VIPP1) is conserved among oxygenic photosynthetic organisms and appears to have diverged from the bacterial PspA protein. VIPP1 localizes to the chloroplast envelope and thylakoid membrane, where it forms homooligomers of high molecular mass. Although multiple roles of VIPP1 have been inferred, including thylakoid membrane formation, envelope maintenance, membrane fusion, and regulation of photosynthetic activity, its precise role in chloroplast membrane quality control remains unknown. VIPP1 forms an oligomer through its amino-terminal domain and triggers membrane fusion in an Mg 2+ -dependent manner. We previously demonstrated that Arabidopsis ( Arabidopsis thaliana ) VIPP1 also exhibits dynamic complex disassembly in response to osmotic and heat stresses in vivo. These results suggest that VIPP1 mediates membrane fusion/remodeling in chloroplasts. Considering that protein machines that regulate intracellular membrane fusion/remodeling events often require a capacity for GTP binding and/or hydrolysis, we questioned whether VIPP1 has similar properties. We conducted an in vitro assay using a purified VIPP1-His fusion protein expressed in Escherichia coli cells. VIPP1-His showed GTP hydrolysis activity that was inhibited competitively by an unhydrolyzable GTP analog, GTPγS, and that depends on GTP binding. It is particularly interesting that the ancestral PspA from E. coli also possesses GTP hydrolysis activity. Although VIPP1 does not contain a canonical G domain, the amino-terminal α-helix was found to be important for both GTP binding and GTP hydrolysis as well as for oligomer formation. Collectively, our results reveal that the properties of VIPP1/PspA are similar to those of GTPases.